Global update: Japan. (November 2011) - Sipp, Doug
Japan continues to be a major player in stem cell biology and related fields, boasting multiple world-class programs in a broad spectrum of stem cell studies, a permissive regulatory framework, an active society for regenerative medicine and a growing industry involvement. The most noted work in recent years has of course originated in the laboratory of Shinya Yamanaka, with the first report of induced pluripotent stem cells (iPS cells) in 2006, and numerous technical advancements since, which prompted the government to establish a Center for iPS Cell Research and Application in 2010 (see below)[1] . Additional concentrations of stem cell research excellence can be found in Tokyo, Osaka, Kobe and Kumamoto. In 2011, Yoshiki Sasai''s laboratory in the RIKEN Center for Developmental Biology, Kobe, achieved another remarkable result in inducing optic cup-like structures from embryonic stem cells using 4D tissue culture techniques, building on previous work in which the group had generated stratified cerebral cortex-like tissue from embryonic stem cells in vitro .